Characterisation of retroviruses in the horse genome and their transcriptional activity via transcriptome sequencing - Brown, Katherine; Moreton, Joanna; Malla, Sunir; Aboobaker, A. Aziz; Emes, Richard D.; Tarlinton, Rachael E. (Elsevier, 2012)
The recently released draft horse genome is incompletely characterised in terms of its repetitive element proﬁle. This paper presents characterisation of the endogenous retrovirus (ERVs) of the horse genome based on a data-mining strategy using murine leukaemia virus proteins as queries. 978 ERV gene sequences were identiﬁed. Sequences were identiﬁed from the gamma, epsilon and betaretrovirus genera. At least one full length gammaretroviral locus was identiﬁed, though the gammaretroviral sequences are very degenerate. Using these data the RNA expression of these ERVs were derived from RNA transcriptome data from a variety of equine tissues. Unlike the well studied human and murine ERVs there do not appear to be particular phylogenetic groups of equine ERVs that are more transcriptionally active. Using this novel approach provided a more technically feasible method to characterise ERV expression than previous studies.